Competing survival analysis for housing relocation behaviour and risk aversion in a resilient housing market - Rashidi, Taha H; Ghasri, Milad
Residential relocation decision making is a complicated process, and modelling this complex course of actions requires careful scrutinisation of different aspects. The relocation decision comprises several different decisions, including the reason for the relocation, relocation timing, and attributes of the desired residence. Among these decisions needing to be taken, the reason for relocation and its timing are decided earlier than others. Depending on the variant reasons and motivations for relocating, its timing may be accelerated or decelerated. Relocation usually occurs because of a multiplicity of reasons, which necessitates using a multivariate model for relocation decision making that is jointly modelled with the timing decision. A competing accelerated failure model to jointly formulate these decisions. The housing search literature emphasizes on the importance of considering financial risk acceptance level of decision makers in residential relocation decision models. Therefore, a binary logit model is used to model whether the decision maker is financially risk averse or not. This paper used longitudinal data collected in Australia from the Household, Income, and Labour Dynamics in Australia Survey. Further, the impact of group decision making on residential relocation is captured in this paper through the information provided in Household, Income, and Labour Dynamics in Australia Survey regarding the manner in which decisions are made within households.
Keywords: Competing hazard model; financial risk aversion; land use; residential relocation